Neuroprotective effect of epidermal growth factor plus growth hormone-releasing peptide-6 resembles hypothermia in experimental stroke. (1st November 2016) - Subirós, N.; Pérez-Saad, H.; Aldana, L.; Gibson, C. L.; Borgnakke, W. S.; Garcia-del-Barco, D.
Abstract: Background: Combined therapy with epidermal growth factor (EGF) and growth hormone-releasing peptide 6 (GHRP-6) in stroke models has accumulated evidence of neuroprotective effects from several studies, but needs further support before clinical translation. Comparing EGF + GHRP-6 to hypothermia, a gold neuroprotection standard, may contribute to this purpose. Objectives: The aims of this study were to compare the neuroprotective effects of a combined therapy based on EGF + GHRP-6 with hypothermia in animal models of ( a ) global ischemia representing myocardial infarction and ( b ) focal brain ischemia representing ischemic stroke. Methods: ( a ) Global ischemia was induced in Mongolian gerbils by a 15-min occlusion of both carotid arteries, followed by reperfusion. ( b ) Focal brain ischemia was achieved by intracerebral injection of endothelin 1 in Wistar rats. In each experiment, three ischemic treatment groups – vehicle, EGF + GHRP-6, and hypothermia – were compared to each other and to a sham-operated control group. End points were survival, neurological scores, and infarct volume. Results: ( a ) In global ischemia, neurological score at 48–72 h, infarct volume, and neuronal density of hippocampal CA1 zone in gerbils treated with EGF + GHRP-6 were similar to the hypothermia-treated group. ( b ) In focal ischemia, the neurologic score and infarct volume of rats receiving EGF + GHRP-6 were also similar to animals in the hypothermia group. Discussion: With hypothermia being a good standard neuroprotectant reference, these results provide additional proof of principle for EGF and GHRP-6 co-administration as a potentially neuroprotective stroke therapy.